Analysis of Diagnostic Assessment in the Science Subject for 4th Grade Elementary School - Pangestuningtyas, Dwi; Nasution, Nasution; Gunansyah, Ganes; Mariana, Neni; Faroh, Nurul Istiq' (Universitas Muhammadiyah Sidoarjo, 2025)
Diagnostic assessment plays a crucial role in the learning process, particularly in identifying students' prior knowledge and learning needs before instruction begins. This study aims to analyze the implementation of diagnostic assessment in the IPAS (Science and Social Studies) subject for fourth-grade elementary school students. A qualitative descriptive approach was used to examine how diagnostic assessments are conducted and their impact on student learning outcomes. Data were collected through classroom observations and student performance analysis. The results indicate that diagnostic assessments help teachers design more effective learning strategies tailored to students’ abilities. However, some teachers do not fully implement diagnostic assessments, leading to disparities in students’ understanding of the material. The findings emphasize the need for proper training and structured implementation of diagnostic assessments to enhance students’ critical thinking skills and improve overall learning outcomes.